Rumba Rules: The Politics of Dance Music in Mobutu s Zaire, Bob W. White, Duke University Press, 2008, 300 pp., paperback: 978-0-8223-4112-3. - Erlmann, Veit (International Library of African Music, 2009)
pages: 166-168
Keywords: African Music